Differences in maximal grip strength and isometric endurance between elite and non-elite young judo athletes - Feriche, B.; Almeida, F.; Bonitch-Gongora, J.; Bonitch-Dominguez, J.; Padial, P. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
In judo, the grip strength is presented as one of the main determinants of success (Franchini et al., 2011). However, scientific literature has not related directly the role of maximal isometric strength (MIS) endurance with the result of the competition. The aim of this study is to compare the behavior of the MIS during an endurance test between elite and non-elite young judo athletes. Method: 45 young judo athletes (U17) were assigned to two groups by their competitive results: medallists (Md) and non-medalists (NMd) in national championships. All participants performed a test to determine the MIS of the dominant hand. After that, subjects executed a MIS endurance test (e-MIS) by performing 8 maximal isometric contractions of 10 s with 10 s of passive rest between them. Results: There were no differences in MIS between both groups (Md: 460.69 ± 92.34 N and NMd: 415.05 ± 70.93 N, p > 0.05). The e-MIS test revealed a significant loss of MIS during the first 3 repetitions in Md and during the first two in NMd (p < 0.001). Along of the 8 repetitions, Md group showed higher MIS values than NMd (p < 0.05). The difference between the 1st and the 8th repetition in the e-MIS test reached 24.47 ± 9.10% in the Md group and 18.81 ± 9.09% in the NMd one. Discussion: The complexity of the technical and tactical actions of the judo combat makes difficult to establish a direct relationship between improved arm strength and success in the competition (Banobic, 2001). The differences observed between groups during the e-MIS test suggest that Md have better strategies to perform maximum levels of MIS in successive grips and/or better recover between them than NMd. Our findings are in agreement with other investigations (Garcia, 2004; Bonitch-Góngora et al., 2007; Franchini et al., 2011), which claim that endurance to the handgrip MIS appears to be the decisive factor to achieve success in judo above its own maximum value.